Factors affecting resilience in Namibian children exposed to parental divorce: a Q-Methodology study - Van Schalkwyk, Janine; Gentz, Shelene (Frontiers in Psychology, 2023)
Introduction: Divorce is a contributor to family instability within sub-Saharan Africa, and specifically within Namibia, an increasing number of children are exposed to its impact. However, not all children react uniformly to the impact of parental divorce and many children may be resilient. Understanding what promotes resilience in children post-divorce in African contexts is vital given the unique socio-cultural context. Therefore, this study aimed to understand how some children are capable of resilience despite exposure to parental divorce in Namibia. Methods: A multiple case study design was employed to assess the lived experiences of children aged 9-12 post-parental divorce, in Windhoek. Using the Child and Youth Resilience Measurement (CYRM-12) scale, 24 children exposed to parental divorce were screened for resiliency. Q-Methodology, with visual material, was utilized with a sub-sample of 12 children who scored high on the CYRM (50% female, mean age=11) to eliminate some of the challenges associated with gathering qualitative data from younger children. For data analysis, the PQ Method 2.35 software program, was used. Results: By-person factor analysis identified four statistically significant profiles. A third (33%) of participants loaded on a factor emphasizing ‘quality parent-child relationships’ and a further 33% emphasizing ‘effective parent conflict resolution’. The final two factors emphasized ‘healthy school attachment’ (17%), and ‘strong community attachment’ (17%). All children emphasized a stable, loving familial environment and frequent visitation with the non-custodial father. Discussion: Our findings suggest that multiple social ecologies nurture resilience in children exposed to parental divorce in Namibia. Support should be extended beyond the perimeters of the nuclear family, and relationships with extended family members, peer groups, school and the wider community can play an important role in children’s adjustment. The study highlights the importance of contextually grounded resilience as some factors that are emphasized for children from more western communities do not reflect as strongly in the results of this study. Other factors, including stronger reliance on community and factors such as the school, peers, and extended family members, may play a bigger role in child resilience post-divorce in Namibia.